Effect of dietary energy concentration, protein: energy and lysine: energy ratios on growth of pigs in the humid tropics - Kuan, K. K.; Mak, T. K.; Farrell, D. J. (CSIRO Publishing, 1986)
Forty-eight Landrace x Large White x Duroc pigs were used in each of two experiments to study the effect of diets with different protein and 1ysine:energy ratios on growth between 20 and 50 kg and on growth, and subsequent carcass characteristics, between 40 and 85 kg. The eight treatments in each experiment comprised a 2x4 factorial design. The factors were digestible energy (DE) of 12.6 and 14.2 MJ/kg diet and four crude protein and lysine levels at each dietary energy level. The diets were based on combinations of traditional feed ingredients and local agricultural byproducts. Daily feed allowance (g) was calculated in both experiments by the formula: 110 Wkg.0.75, where W is liveweight. Pigs given high-energy diets grew faster, with a better feed conversion ratio, than those given the low-energy diets. In both experiments, growth rate of pigs was faster and feed conversion efficiency improved linearly (P<0.05) with increasing protein:energy ratio. Mean feed and DE intakes were the same on all treatments within an experiment. For pigs at 85 kg, killing-out percentage declined with increasing protein : energy ratio. Eye muscle area increased and back-fat thickness decreased as the protein and lysine contents of the diets increased. It appears that a protein (g):energy (MJ DE) ratio of about 15.1 for growing pigs, and 12.7 for finishing pigs, optimises performance. Corresponding total lysine (g): energy (MJ DE) ratios were 0.7 1-0.77 and 0.63-0.64, respectively.